Peran Lembaga Penyiaran Televisi Dalam Kampanye Pemilihan Umum Presiden dan Wakil Presiden - Marnia Rani (Jurnal Selat, 2014)
Television broadcasters that use the public property has a very important role in the process of delivering information to the public. Informing it must be done in a fair and balanced in order to function as a medium of social control and political education for the community. However, what happens when the television is nothing more than a political mouthpiece and owners of capital. This phenomenon is extremely worrisome, because in fact the media should be fair and impartial to any political interest. For that, we need a regulation governing the activities of the general election campaign for president and vice president on television. In addition, the implementation of regulatory oversight should also be carried out by various parties related to news and election campaign ad for president and vice president on television. Keywords: Broadcasting Agency, Campaign Presidential Election